Michel Foucault: The Constitution of the Modern Disciplinary Subject - Kiosoglou, Thanos (Conatus - Journal of Philosophy, 2017)
In his seminal Discipline and Punish: The Birth of the Prison, Michel Foucault aims at outlining the historical course that led to the promulgation and consolidation of the institution of imprisonment as a means of punishment as well as narrating how the corresponding human type, i.e. the contemporary disciplined subject, has been shaped. Obviously, the disciplined subject gradually took the place of the tormented subject. Consequently, this study aims at describing the sequential mutations of the imposed punishment as it progressively shifted from the spectacular slaughtering of the body to the strictly scientific manipulation of the non-material dimension of the human being. The reformation of the punitive practices “constructs” a docile body. It must be noticed, however, that this body is not necessarily guilty, since the disciplinary schemes concern everybody, even the most innocent sides of the everyday life as for example the hospital, the school or the barracks. Additionally, discipline is imposed through the division of the space, what Foucault calls the “art of allocation”, so that every working person is easily seen and supervised by the eye of the authority, while the disciplined subject is being forged gradually through the sense of responsibility before the flowing time. Foucault highlights the “political technology of the body”, that is its usurpation by the authorities, who aim at imposing to it adictated activity that produces palpable results in a binding frame of time. Although selective and brief, the present account of the punitive concepts of the three last centuries clarifies the fact that the authoritarian strategies are indissolubly interwoven with the different connotations of the human body, through the use of which they subdue human beings.